Pengaruh Perilaku Konsumen, Word Of Mouth, dan Labelisasi Halal Berdasarkan Konsep Syariah Terhadap Keputusan Penggunaan Jasa Grab-Food di Kota Jambi - Hani Yustina; Titin Agustin Nengsih; Syahril Ahmad (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aimed to determine the effect of consumer behavior, word of mouth, and halal labeling on the decision to use Grab Food services. The population in this study are consumers who use Grab Food services. The sample in this study were 96 consumers who were obtained through the sampling technique with the Lemeshow method. The data collection method uses a questionnaire which is distributed to all consumers and the data is processed using multiple linear regression analysis. The results of multiple linear analysis show that consumer behavior, word of mouth, and halal labeling have a positive and significant effect on the decision to use grab food services. This research is expected to increase knowledge regarding consumer behavior, word of mouth, and halal labels in using Grab Food services and maintain good relations with consumers by maintaining the quality of products and services that can be used to make usage decisions.